Inovasi dan Kebijakan Pendidikan: Subjektivitas dan Objektivitas Kebijakan Pendidikan - Harist, Hidayatullah Yahmad; Sirozi, Muhammad (Jurnal Ilmiah Global Education, 2025)
The rapid and dynamic changes of the modern era have significantly impacted the field of education, demanding a system that is more adaptive, innovative, and responsive to both global and local challenges. Twenty-first-century education emphasizes the importance of critical thinking, communication, and collaboration skills, which can only be achieved through innovation in educational approaches, methods, and policies. On the other hand, educational policy serving as a guiding framework for the system is often influenced by subjectivity, such as political interests, ideological bias, and bureaucratic structures, which can undermine objectivity in decision-making. This study employs a descriptive qualitative approach through library research to examine the role of innovation as well as the dynamics of subjectivity and objectivity in educational policymaking. The findings indicate that while subjectivity cannot be completely eliminated, participatory, transparent, and data-driven policymaking can lead to a more equitable and effective education system. Continuous innovation and evaluation are also essential to meet the evolving needs of society, particularly in the context of religious education and character development.